Arab Schools And High School Students' Level Of Knowledge Of The Arabic Language: Dar Al Uloom As A Model/ Ø§Ù„Ù…Ø¯Ø§Ø±Ø³ Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙˆÙ…Ø³ØªÙˆÙ‰ Ø§Ù„Ø·Ù„Ø¨Ø© Ø§Ù„Ø«Ø§Ù†ÙˆÙŠØ© ÙÙŠ Ù…Ø¹Ø±ÙØ© Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ©: Ø¯Ø§Ø± Ø§Ù„Ø¹Ù„ÙˆÙ… Ù†Ù…ÙˆØ°Ø¬Ø§ - Mahmoud-Mukadam, Abdur-Rasheed; Imam, Muritala Akeyede (Ijaz Arabi Journal of Arabic Learning, 2020)
The teaching of the Arabic language had different stages before the university stage, which is passed by all who hope to master this honourable language, including the primary, preparatory and secondary stages. For those who want to mature in this education left some of those stages of arrogance and wonder and arrogance, because it must ultimately have an undesirable effect. Therefore, this paper seeks to highlight the efforts of Dar Al Uloom in Ilorin towards its secondary students to learn this Arabic language by answering the following questions: What are the reasons why Dar Al Uloom students distinguish among their peers? What curricula did Dar Al Uloom influence to study Arabic? Is there a prestigious scientific place for students of Dar Al Uloom in an Islamic society? Moreover, how did Dar Al Uloom achieve that honourable Al-Otim in the literary and scientific field? This paper will undoubtedly answer each of these advanced questions in its scientific journey from this study.